2019
DOI: 10.1186/s40529-019-0260-3
|View full text |Cite
|
Sign up to set email alerts
|

Studies of a rice sterile mutant sstl from the TRIM collection

Abstract: Background Rice ( Oryza sativa ) is one of the main crops in the world, and more than 3.9 billion people will consume rice by 2025. Sterility significantly affects rice production and leads to yield defects. The undeveloped anthers or abnormal pollen represent serious defects in rice male sterility. Therefore, understanding the mechanism of male sterility is an important task. Here, we investigated a rice sterile mutant according to its developmental morphology and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
1
0
1
Order By: Relevance
“…This phenomenon is due to spontaneous outcrossing occurring in different generations in the rice fields [54]. While screening for novel phenotypes in Taiwan Rice Insertional Mutagenesis (TRIM) population, Chang et al 2019, identified a semi-sterile mutant ( sstl ), however, it was later found to be associated with an un-tagged T-DNA line [55].…”
Section: Rice T-dna Mutant Databases and Toolsmentioning
confidence: 99%
“…This phenomenon is due to spontaneous outcrossing occurring in different generations in the rice fields [54]. While screening for novel phenotypes in Taiwan Rice Insertional Mutagenesis (TRIM) population, Chang et al 2019, identified a semi-sterile mutant ( sstl ), however, it was later found to be associated with an un-tagged T-DNA line [55].…”
Section: Rice T-dna Mutant Databases and Toolsmentioning
confidence: 99%
“…出す.よって,劇的にコピー数を増加させる可能性があ り,植物ゲノムの拡大にも寄与してきたことが推察され る Bennetzen 1999, Bento et al 2013 (Kumar and Bennetzen 1999, Feschotte et al 2002, Havecker et al 2004 (Kumar and Hirochika 2001, Schulman et al 2004, Kalendar et al 2011, Poczai et al 2013 れる (Flavell et al 1998, Kalendar et al 1999, Waugh et al 1997, Syed et al 2005 (Kumar and Bennetzen 1999, Feschotte et al 2002, Slotkin and Martienssen 2007, Lisch 2009) .その理由としては,変異を引き起こす可能 性のあるトランスポゾンに対して,宿主ゲノムが DNA のメチル化やクロマチン修飾等のエピジェネティック な制御機構を進化させてきたためであると考えられてい る ( Slotkin andMartienssen 2007, Lisch 2009 (Marquet et al 1995, Mak and Kleiman 1997, Kelly et al 2003, Hizi 2008 (Ukoskit and Thompson 1997, Kriegner et al 2003, Cervantes-Flores et al 2008, Zhao et al 2013 (Ukoskit and Thompson 1997, Kriegner et al 2003, Cervantes-Flores et al 2008, Chang et al 2009, Li et al 2010, Zhao et al 2013…”
unclassified